In Vitro Effectiveness of Neem Oil (Azadirachta Indica A. Juss) Shampoo as Anti Head Lice (Pediculus humanus capitis) - Norisca A. Putriana; Azizul Hakim; Patihul Husni; Taofik Rusdiana (Universitas Padjadjaran, Indonesia)
Head lice (Pediculus humanus capitis), a parasite causing hair problem, often occurs in society.The study aimed to evaluate in vitroeffectiveness of shampoo formulation containing neem oil as an anti head lice. An experimental method was used to examine the formulation of shampoo, irritation test, testing the effectiveness of shampoo against head lice (Pediculicidal activity), and testing the effectiveness of shampoo against nits (Ovicidal activity). The effectiveness test employed an in vitromethod where neem oil shampoo were tested directly towards head lices and nits isolated from humans, then the mortality was observed. To recognize the safety of the shampoo, skin and eye irritation tests were carried out by applying 0.5 ml on the skin and dripping 0.1 ml shampoo into New Zealand white rabbit’s eyes.Data were analyzed using Kruskal Wallis and Mann Whitney. The study results showed that the primary irritation index for 5%, 10%, 15%, and 20% neem oil shampoo were 0; 0111; 0.222; and 0.222, respectively. All of the shampoos were very mild irritation response category. Eye irritation tests showed that only the 20% neem oil shampoo gave a mild irritation response with degree of corneal opacity ≥ 1 and recovered after 7 days of observation. The 5%, 10%, 15%, and 20% neem oil shampoo were effective as an anti head lice. The 15% and 20% neem oil shampoo had anti head lice effectiveness activity as same as 1% permethrin lotion. In conclusion, the 15% neem oil shampoo was chosen as the best shampoo, its high anti head lice effect and light irritation response. Keywords: Head lice, neem oil (Azadirachta indica A. Juss), shampoo